2012
DOI: 10.1088/0004-637x/754/1/27
|View full text |Cite
|
Sign up to set email alerts
|

A New Low Magnetic Field Magnetar: The 2011 Outburst of Swift J1822.3–1606

Abstract: We report on the long-term X-ray monitoring with Swift, RXTE, Suzaku, Chandra, and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
175
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(188 citation statements)
references
References 59 publications
12
175
1
Order By: Relevance
“…Subsequently, the source was followed by virtually all the current generation of Xray satellites. The results of the first 9 months of X-ray monitoring of this new magnetar were presented and discussed by Rea et al (2012;hereafter R12), Scholz et al (2012) and Scholz et al (2014). In this work we perform an unprecedent coherent, pulse phase resolved spectroscopy (PPS) analysis spanning more than 400 days of outburst decay (see Fig.…”
Section: Swift J18223-1606mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the source was followed by virtually all the current generation of Xray satellites. The results of the first 9 months of X-ray monitoring of this new magnetar were presented and discussed by Rea et al (2012;hereafter R12), Scholz et al (2012) and Scholz et al (2014). In this work we perform an unprecedent coherent, pulse phase resolved spectroscopy (PPS) analysis spanning more than 400 days of outburst decay (see Fig.…”
Section: Swift J18223-1606mentioning
confidence: 99%
“…Two more low-field magnetars were recently discovered thanks to their outburst activity, 3XMM J185246.6+003317 (Zhou et al 2014, Rea et al 2014) and SWIFT J1822.3-1606 (Rea et al 2012;Scholtz et al 2012). The latter source was studied through the long-term monitoring that we present in this work.…”
Section: Introductionmentioning
confidence: 99%
“…2 for this specific value of the temperature. XMM-Newton satellites found that SGR 1822-1606 rotates with a period of P = 8.44 s and slows down at a rateṖ = 9.1 × 10 −14 (see Rea et al 2012, for details). The corresponding rotation angular velocity of the source is Ω = 2π/P = 0.74 rad s −1 .…”
Section: Prediction Of the Spindown Ratementioning
confidence: 99%
“…(10), which are to be considered to be predictions of the white dwarf model because they were presented in advance of the observational results given in (Rea et al 2013). The situation has become even more striking considering the X-ray timing monitoring with Swift, RXTE, Suzaku, and XMM-Newton satellites of the recently discovered SGR Swift J1822.3-1606 (Rea et al 2012). The rotation period P = 8.437 s and the spindown rateṖ = 9.1×10 −14 were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding author: D. Hadasch, hadasch@ieec.uab.es magnetic fields (∼10 14 −10 15 Gauss) that are ∼10−1000 times higher than the average value in radio pulsars, near or even above the quantum electrodynamic field strength, B QED = m 2 e c 3 /e ∼ 4.4 × 10 13 G (Harding & Lai 2006), although with two exceptions (Rea et al 2010(Rea et al , 2012. They have bright X-ray luminosities (L x ∼ 10 32 −10 36 erg s −1 ) from 0.1-300 keV, longer rotation periods than most ordinary radio pulsars (∼2-12 s), and very high period derivatives (∼10 −13 -10 −11 s s −1 ).…”
Section: Introductionmentioning
confidence: 99%